The Littoral of the Terek-Kuma Lowland of Republic of Dagestan – an Ecotone in the System of Modern Knowledge (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The littoral of the Terek-Kuma lowland in Republic of Dagestan is an ancient territory which was subjected to numerous catastrophes associated with extinction of the Tethys Ocean. Hydrophytes had a large taxonomic diversity in Paleogene and Neogene. In Sarmatian Basin genera Euryale and Brasenia disappeared at the beginning of Pliocene as a result of borealization and climate continentalization. The initial macrothermal forms in genera Nymphaea, Nuphar, Stratiotes, Ceratophyllum, Trapa, Azolla, Salvinia and Marsilea disappeared. The connection of the Caspian Sea with eastern seas and western basin was disrupted in Oligocene. From akchagyla the oecesis and the spreading of hydrophytes was repeatedly interrupted because of instability of the Caspian Sea and anthropogenic factors that resulted in decrease of the species formation in families Trapaceae и Nelumbonaceae. Hydrophytobiota in the littoral of the Terek-Kuma lowland is rather vulnerable. Instability of the environment factors which are important for its existence a specific composition and structure of the ecotone in the Tura floristic province was determined.
Keywords: ecotone, history, development, catastrophe, littoral, Caspian Sea.